2014
DOI: 10.1159/000365194
|View full text |Cite
|
Sign up to set email alerts
|

Antiherpetic Mechanism of a Sulfated Derivative of <b><i>Agaricus brasiliensis</i></b> Fruiting Bodies Polysaccharide

Abstract: Objective: To study the anti-herpes simplex virus (HSV) activity of a (1→6)-(1→3)-β-D-glucan isolated from Agaricus brasiliensis fruiting bodies (FR) as well as its chemically sulfated derivative (FR-S). Methods: The antiherpetic activity and mechanism of action was studied by viral plaque assay applying different methodological strategies. Results: Although FR presented no in vitro antiherpetic action at 1 mg/ml, FR-S displayed promising anti-HSV-1 and anti-HSV-2 activities in both simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Yamamoto et al (2013) found an anti-HSV-1 activity under simultaneous (EC 50 ¼ 454 mg/mL) and postinfection (83.6 % of inhibition at 800 mg/mL) treatments with PLS, using a viral plaque number reduction assay. Nonetheless, neither anti-HSV-1 nor anti-HSV-2 activity under these two treatments was found for FR at the maximum tested concentration (1 mg/ml) (Cardozo et al 2014).…”
Section: Polysaccharides and Antiviral Activitymentioning
confidence: 75%
See 1 more Smart Citation
“…Yamamoto et al (2013) found an anti-HSV-1 activity under simultaneous (EC 50 ¼ 454 mg/mL) and postinfection (83.6 % of inhibition at 800 mg/mL) treatments with PLS, using a viral plaque number reduction assay. Nonetheless, neither anti-HSV-1 nor anti-HSV-2 activity under these two treatments was found for FR at the maximum tested concentration (1 mg/ml) (Cardozo et al 2014).…”
Section: Polysaccharides and Antiviral Activitymentioning
confidence: 75%
“…FR-S had had no detectable protein content and lower molecular weight (127 kDa) in comparison to the non-sulfated version ). The introduction of sulfated groups on FR resulted in a sulfated derivative (FR-S) with promising in vitro antiherpetic activity (EC 50 < 6.74 mg/mL), acting by inhibition of HSV-1 and HSV-2 adsorption, penetration, and cell-tocell spread (Cardozo et al 2014). In a different way, SPLS did not demonstrate much improvement on antiviral activity after sulfation in the simultaneous treatment (EC 50 ¼ 346 mg/mL) and had no activity in the postinfection treatment (Yamamoto et al 2013).…”
Section: Polysaccharides and Antiviral Activitymentioning
confidence: 99%
“…Sulfated compounds isolated from a polysaccharide (MI-S) derived from Agaricus brasiliensis have shown antiherpetic activity against HSV-1 and HSV-2 (De Sousa Cardozo et al, 2014). MI-S inhibited viral adsorption and penetration into Vero cells and had a synergistic effect with acyclovir (De Sousa Cardozo et al, 2014).…”
Section: Fungus-derived Compounds With Antiviral Activity Against Hsvmentioning
confidence: 99%
“…Fungal and oat β-glucans exhibit in vitro antiherpetic activity and inhibit viral adsorption, penetration, and cellto-cell spread [11,25,26] and increase the macrophage proinflammatory cytokine response to HSV-1 infection [27]. erefore, they may represent potential prophylactic/ treatment agents in HSV-1 infection and can decrease susceptibility to viral infection following oral administration of β-glucans.…”
Section: Introductionmentioning
confidence: 99%